Toward implementing the CLIL approach at the CHMS School (Colegio Hebreo Monte Sinai) in Mexico City: An intervention proposal for 7th grade Biology course - Gamero-Calderón, Andrea (My University, 2018)
In this Master’s Dissertation, we present CLIL (Content and Language Integrated Learning) as an approach that promotes motivation for the students, bringing; as a result, a positive attitude toward subject and language learning in a cross-curricular way. In Mexico, there is a need for learning English due to globalization and because of its geographical location to the United States of America and Canada. Government authorities and schools are putting much emphasis on delivering bilingual programs, adapting them to different contexts. The purpose of this Master's Dissertation is to present CLIL as an innovative approach to teaching Biology through the English language at the Colegio Hebreo Monte Sinai Secondary School. Identifying, the core features and making the school aware of its potential and the benefits that it has mainly around Europe and some countries around the world and that some private schools in Mexico have already implemented it in Secondary Education. The school, with coordination between the entire learning community, can move forward with an effective strategy to achieve this goal.This proposal efficiently sets its basis that hints the interest of students in learning a second language, making content more enjoyable to acquire, which helps them to become skilled citizens in society.
Keywords: bilingual education; education in Mexico; content teachers; biology course; secondary education; Máster Universitario en Educación Bilingüe